Job satisfaction among secondary school teachers in Tanzania : the case of Njombe district - Ngimbudzi, Fredy Wilson (2009)
The purpose of this study is to examine the factors that are associated with teachers‟ job satisfaction. A study sample of 162 (N=162) teachers was surveyed. The descriptive statistics techniques revealed that teachers are satisfied with aspects under the following dimensions: social benefits, meaningfulness of the job and support from administration. Conversely, the teachers indicated they are least satisfied with the aspects under the job characteristics dimension. Additionally, the independent t-test and MANOVA revealed significant differences in teachers‟ job satisfaction in relation to gender, age, school location and school type, but there are no significant differences in relation to marital status, teaching experience, teacher type and promotional position in all the five core job dimensions. Moreover, the stepwise regression model revealed that the meaningfulness of the job and job characteristics dimensions contributed significantly to teachers‟ intention to remain in the job. Lastly, the bivariate correlation (Pearson r) revealed that there is a significant relationship between job satisfaction and the five job dimensions: job characteristics, social benefits, meaningfulness of the job, support from administration and intention to remain in the job. These findings are both consistent and inconsistent with the previous research findings. This study was done for school administrators, employers, policy makers, planners and school owners in Tanzania and other countries.